Respuesta :
A. 2(-3) - 7 = -1
-6 - 7 = -1
-13 = -1
wrong
B. 3(-3) + 8 = 1
-9 + 8 = 1
-1 = 1
wrong
C. 1/2 (-3) + 8 = 10
-3/2 + 8 = 10
-3/2 = 2
wrong
D. 1/2 (2(-3) - 6) = -6
1/2 (-6 - 6) = -6
1/2 (-12) = -6
-12/2 = -6
-6 = -6
correct
D is the answer
-6 - 7 = -1
-13 = -1
wrong
B. 3(-3) + 8 = 1
-9 + 8 = 1
-1 = 1
wrong
C. 1/2 (-3) + 8 = 10
-3/2 + 8 = 10
-3/2 = 2
wrong
D. 1/2 (2(-3) - 6) = -6
1/2 (-6 - 6) = -6
1/2 (-12) = -6
-12/2 = -6
-6 = -6
correct
D is the answer
Well A.2x-7=-1 equals x=3
And B.3x+8=1 equals x=- 7/8
And C. 1/2x+8=10 equals x=4
And D. 1/2 (2x-6)=-6 equals x=-3
So you’re answer is D. 1/2 (2x-6)=-6